Strategi Komunikasi Untuk Harmonisasi Sosial Pada Anak Sekolah Dasar Dalam Konteks Multikulturalisme - Khalishaa Zhafira; Wanda Habibah Al Zahwa; Janera Maharani; Billy Dwy Nugraha Haryono; Yessika Felicia Lumban Tobing; Ester Melvin Yansria Mendrofa (Jurnal Merah Putih Sekolah Dasar, 2026)
This study aims to examine communication strategies that support the creation of social harmony in multicultural communities, particularly among elementary school students. The approach used is a qualitative descriptive study employing literature review and direct observation at SD Negeri 057221 in Lalang Village, Tanjung Pura Subdistrict, Langkat Regency, North Sumatra. Data were obtained through analysis of academic literature as well as student interactions during learning activities and group games. The results indicate that cultural diversity in elementary schools can serve as a constructive potential if managed through inclusive, adaptive, and dialogic communication. Observations revealed that children interact more easily when engaged in light-hearted games, which foster cooperation, empathy, and mutual respect. Minor instances of stereotyping and teasing among students were still observed, but these can be minimized through teacher-guided interactive communication strategies. Thus, communication strategies serve not only as a means of conveying messages but also as a primary mechanism for building social solidarity and strengthening character education amidst diversity.